Managerial Response and Recovery in Online Service Setting: An Other-Customer Perspective - Ma, Ke; Zhong, Xin (Journal of Marketing Development and Competitiveness, 2020)
Most of the literature on service failure and recovery assesses the effectiveness from the perspective of customers. Little is known about how the failure of other customers and recovery experiences influence the focal customer’s recovery attitude. This research employs an experimental design to examine how the moderating role of managerial responses impacts on the focal customer’s recovery attitude in online service settings. Its findings suggest managerial responses play a moderating role. It is also found that not all customers are sensitive to online managerial responses and that only field-dependent customers show concern for other-customer service experience.